Pengaruh Body Image Terhadap Alienasi pada Remaja Perempuan (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to find out how body image influences alienation among adolescent girls in Sumbawa Besar district. This research uses a descriptive quantitative approach. The sampling technique used purposive sampling of 269 samples. The research instrument consists of two scales, namely the body image scale and the alienation scale. Based on the findings of research conducted in Sumbawa Besar Regency, it can be said that the body image variable has a small influence on alienation with a coefficient of determination (R square) value of 0.456. and the two variables have a strong relationship based on the correlation coefficient (R) value, which is 0.676. There is an influence of body image on alienation among female teenagers in Sumbawa Besar district. The result is a significant n of 0.000 (